An Overview on NO-Rich Diet for Lifestyle-Related Diseases - Kobayashi, Jun; Ohtake, Kazuo; Uchida, Hiroyuki (Highlights on Medicine and Medical Research Vol. 1, 2021)
Decreased nitric oxide (NO) availability due to obesity and endothelial dysfunction might be causally related to the development of lifestyle-related diseases such as insulin resistance, ischemic heart disease, and hypertension. In such situations, instead of impaired NO synthase (NOS)-dependent NO generation, the entero-salivary nitrate-nitrite-NO pathway might serve as a backup system for NO generation by transmitting NO activities in the various molecular forms including NO and protein S-nitrosothiols. Recently accumulated evidence has demonstrated that dietary intake of fruits and vegetables rich in nitrate/nitrite is an inexpensive and easily-practicable way to prevent insulin resistance and vascular endothelial dysfunction by increasing the NO availability; a NO-rich diet may also prevent other lifestyle-related diseases, including osteoporosis, chronic obstructive pulmonary disease (COPD), and cancer. This review provides an overview of our current knowledge of NO generation through the entero-salivary pathway and discusses its safety and preventive effects on lifestyle-related diseases. Although the role of diet-derived NO activity in lifestyle-related diseases is complex and remains to be fully elucidated, the intake of nitrate as a nutrient in vegetables might be beneficial to human health as a result of synergistic effects with other nutrients present in vegetables, and would be recommended as a nutritional approach to the prevention and treatment of the lifestyle related diseases.